(untitled) (Research, Society and Development, 2021)
Exposure to stressful factors plays an important role in development of depressive disorders. The deleterious effects of stress on neuroplasticity and apoptosis can be accentuated by chronic use of antidepressants. Thus, this study aims to evaluate and correlate the effects and consequences of physical stress (PS), associated with the treatment of fluoxetine hydrochloride (FC), on brain volume and cortical thickness of three brain areas. Brains of 25 male Wistar rats (Rattus norvegicus) were used. These animals were divided into 5 groups: G1 – control group; G2 – FC and without PS; G3 – PS but without FC; G4 –FC until the day before surgical procedure (PS); and G5 – Animals treated with FC until 30 days after surgical procedure (PS). The results show that groups G3, G4 and G5 had a significant reduction in brain volume. Regarding cortical thickness in limbic area, the data show that groups G4 and G5 had a significant reduction compared to G1, as well as groups G3, G4 and G5 showed a significant difference compared to G2. In the sensitive area, groups G3, G4 and G5 had a significant reduction when compared to G1; the same was observed for G4 and G5 in relation to groups G2 and G3. In the motor area, a similar result was observed in groups G3 and G4 in relation to G1. The data allow to conclude that physical stress, associated or not with chronic use of fluoxetine hydrochloride, decreases the cortical volume of male rats brain and, as a consequence of reduction, there is a significant loss of cortical density in limbic, sensory and motor areas.